The C-532T polymorphism of the angiotensinogen gene is associated with pulse pressure: a possible explanation for heterogeneity in genetic association studies of AGT and hypertension. - Baker, M; Rahman, T; Hall, D; Avery, P; Mayosi, B; Connell, J; Farrall, M; Watkins, H; Keavney, B (2007)
BACKGROUND: Many previous studies have investigated whether there is an association between genotypes at the angiotensinogen (AGT) gene and hypertensive status, but few have incorporated quantitative data. Although meta-analyses support a possible effect of AGT variants on blood pressure (BP), substantial unexplained between-study heterogeneity has been observed. We hypothesized that a primary effect of AGT variants on arterial stiffness (and thus pulse pressure) might explain such heterogeneity, and tested for such an effect in a family study. METHODS: We studied 1425 individuals from 248 families ascertained through a proband with essential hypertension. BP was measured using 24 h ambulatory monitoring, and polymorphisms of the AGT gene that had been previously associated with hypertension and/or plasma angiotensinogen levels were typed. Pulse pressure was used as a measurement of arterial stiffness. RESULTS: We observed a highly significant association between genotypes at the AGT C-532T polymorphism and pulse pressure (p = 0.00006). Each T allele was associated with a 5% lower pulse pressure (that is, an additive effect). This resulted from opposing genotypic effects to (slightly) lower systolic BP and (slightly) elevate DBP. CONCLUSIONS: These results suggest that genetic variation at the angiotensinogen locus may primarily affect arterial stiffness, and therefore pulse pressure. The heterogeneity between previous genetic studies of AGT and hypertension status could in part be explained by this finding, since case selection criteria based on systolic BP, diastolic BP, or both would result in different levels of selection for the -532T allele.